P29 Outcomes after hospitalisation with spontaneous bacterial peritonitis over a 13-year period: a retrospective cohort study. (20th September 2022) - Ubhi, Nicholas; Mourad, Adele; Tausan, Matija; Lewis, Declan; Smethurst, James; Wenlock, Rhys; Gouda, Mahmoud; Bremner, Stephen; Verma, Sumita
Abstract : Spontaneous bacterial peritonitis (SBP) is associated with high morbidity and mortality. 1 This study aimed to assess outcomes in patients with an index presentation of SBP over a 13-year period in Southeast England. This retrospective cohort study collected data on all patients admitted with SBP from June 2006-May 2019. Patient records were reviewed and divided into period 1 (June 2006-November 2012) and period 2 (December 2012-May 2019), to assess differences, if any, in outcomes. The primary outcome was overall mortality. Cox proportional hazards regression and Kaplan-Meier survival analysis were performed. During the study period, 185 patients were hospitalised with SBP, 66%(n=123/185) being male, mean±SD age 57.9±13.3 years with alcohol being the most common cause of cirrhosis (76%, n=140/185). Mean MELD and UKELD scores were 24.0±7.1 and 59.6±7.0 respectively. In 22%(n=40/185) SBP was the index presentation of cirrhosis. Overall mortality was 85%(n=157/184), 1, 2 and 3-year survival being 34%, 28% and 25% respectively. Independent predictors of overall mortality were age (HR 1.028, 95% CI 1.011–1.045, p=0.001), serum creatinine (HR 1.003, 95% CI 1.000–1.005, p=0.018), positive ascitic fluid culture (HR 1.709, 95% CI 1.161–2.514, p=0.007) and hepatic encephalopathy (HR 1.703, 95% CI 1.040–2.789, p=0.034). Inpatient mortality was 35%(n=64/185), independent predictors being serum creatinine (HR 1.003, 95% CI 1.000–1.006, p=0.037), smoker on admission (HR 2.023, 95% CI 1.114–3.673, p=0.021) and ascitic fluid neutrophil count (HR 1.0001, 95% CI 1.0000–1.0002, p=0.006). Of those surviving hospitalisation, 78%(n=93/120) died during a median follow-up of 11.5 months (IQR 39.6). Comparing period 1 vs. period 2, follow-up duration (months, IQR) was similar (3.7, 21.8 vs. 2.2, 25.1, p=0.298). The latter however had lower serum sodium (mmol/L) (130.3±7.3 vs. 133.3±6.3, p=0.003) and ascitic fluid albumin (g/L) (6.2±3.4 vs. 10.8±5.5, p<0.001), higher ascitic fluid neutrophil count (cells/mm 3, IQR) (650, 2286 vs. 400, 850, p<0.001), were more likely to receive intravenous albumin (86%(n=80/93) vs. 57%(n=52/92), p<0.001) and more likely to have hepatorenal syndrome (55%(n=51/93) vs. 33%(n=30/92), p=0.002). Prevalence of drug-resistant bacteria was 45% vs. 38% (period 1 vs. period 2 respectively) (p=0.521). Mortality overall and in those surviving hospitalisation was greater in period 1, 96%(n=87/91) vs. 75%(n=70/93), p<0.001 and 93%(n=54/58) vs. 63%(n=39/62), p<0.001 respectively. SBP continues to be associated with high mortality, serum creatinine being an independent predictor of both overall and inpatient mortality. However, mortality appears to have declined over the last 13 years, despite more severe initial presentations. Reference: Aithal G, Palaniyappan N, China L, Härmälä S, Macken L, Ryan J et al. Guidelines on the management of ascites in cirrhosis. Gut . 2020;70 (1):9–29.